Fontes de silício para o controle de Meloidogyne javanica em diferentes espécies vegetais - Mattei, Danielle (2015)
Currently safer alternatives for controlling pests and diseases in agriculture and products with lower toxicity have been prioritized, for exemple the use of products, biotic or abiotic, in order to increase the resistance of plants to disease has been the focus of numerous studies, including the use of silicon (Si) to control nematoses. Therefore, the study evaluated three different sources of Si (Silifort®, Rocksil® and wollastonite) on penetration, development and reproduction factor (RF) of Meloidogyne javanica, maize and rice, accumulators, and beans and soybeans, not accumulators of Si, and the production of phytoalexins in sorghum and beans. The seedlings were transplanted and treated with the solutions Silifort® and Rocksil®. The wollastonite was applied to the soil 10 days before the transplanting, and the soil was drenched until the transplant. The inoculation was performed ten days after the transplant, with 1000 eggs and eventual juveniles (J2) of M. javanica. Plant samples were evaluated at 3, 8, 13 and 18 days to determine the number of specimens and stage of g-1 root. The RF was evaluated in these cultures and sorghum, 60 days after of inoculation (DAI), when it also evaluated the height, top dry matter (TDM), fresh root matter (FRM), nematodes per plant, nematode.g-1 root. This experiment was repeated in two periods (experiments 1 and 2). The evaluation of the production of phytoalexins in beans and sorghum, was conducted using the treatments with Si and water as control. Initially the wollastonite favored the penetration and development of M. javanica on rice and beans, while in soybeans all treatments reduced the development, but only Silifort® reduced the penetration. Thirteen DAI, the wollastonite favored the development and penetration. Eighteen DAI, rice, beans and soybeans had less development of M. javanica when treated with Rocksil®, Silifort® and wollastonite. All sources of Si reduced penetration of rice, but only Silifort® and wollastonite affected penetration in bean and soybean, respectively. The maize did not provide answers to the use of Si.